2022
DOI: 10.3847/1538-4357/ac87a9
|View full text |Cite
|
Sign up to set email alerts
|

Call and Response: A Time-resolved Study of Chromospheric Evaporation in a Large Solar Flare

Abstract: We studied an X1.6 solar flare produced by NOAA Active Region 12602 on 2014 October 22. The entirety of this event was covered by RHESSI, IRIS, and Hinode/EIS, allowing analysis of the chromospheric response to a nonthermal electron driver. We derived the energy contained in nonthermal electrons via RHESSI spectral fitting and linked the time-dependent parameters of this call to the response in Doppler velocity, density, and nonthermal width across a broad temperature range. The total energy injected was 4.8 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
2
4
0
Order By: Relevance
“…This suggests a transition from explosive to gentle evaporation. The durations of the fast and gentle velocity phases are consistent with previous reports (Fletcher et al 2013;Sellers et al 2022). The decrease in the nonthermal velocity for CE2 occurs without a significant decrease in the Doppler velocity, which suggests the presence-and corresponding reductionof turbulence (Polito et al 2019).…”
Section: Iris Spectra Of the Chromospheric Evaporationsupporting
confidence: 90%
“…This suggests a transition from explosive to gentle evaporation. The durations of the fast and gentle velocity phases are consistent with previous reports (Fletcher et al 2013;Sellers et al 2022). The decrease in the nonthermal velocity for CE2 occurs without a significant decrease in the Doppler velocity, which suggests the presence-and corresponding reductionof turbulence (Polito et al 2019).…”
Section: Iris Spectra Of the Chromospheric Evaporationsupporting
confidence: 90%
“…In the footpoint of a C class flare, ions forming T > ∼1.5 MK exhibited large blueshifts whereas T < ∼1.5 MK exhibited redshifts (assuming ionisation equilibrium for their formation temperatures). Studying an Xclass flare in which EIS observed several footpoint sources (Sellers et al, 2022) found similar results but with a range of flow reversal temperatures T FR ∼[1. 35-1.82] MK.…”
Section: "Electron Beam" Driven Mass Flowsmentioning
confidence: 66%
“…As such, EUVST is very well placed to perform detailed studies of mass flows during flares that encompass simultaneously the chromosphere, transition region, and corona (with each layer sampled by many lines). Comprehensive analyses such as those performed by Milligan and Dennis (2009) and Sellers et al (2022) over this wide temperature range, and with higher spatiotemporal resolution, should be a priority to better understand the evolution of mass flows in flares. EUVST will be complemented by observations from the Multi-slit Solar Explorer (MUSE;De Pontieu et al, 2020;Cheung et al, 2022) which has a more limited temperature coverage, focussing on the corona and flare plasma, with one line sampling the transition region, but which has 37 slits, allowing imaging spectroscopy of an entire active region sized field of view to be performed in <12 s. MUSE observations of the flaring corona, covering the full flaring structure, will hopefully shed light on continued energy release in the post-impulsive phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of explosive chromospheric evaporation, chromospheric plasmas are rapidly heated, resulting in a much higher pressure in the chromosphere. Then, some plasmas expand upward into the low-density corona at fast velocities of several hundred km s −1 , while some other plasmas precipitate downward with a slow velocity of a few tens km s −1 into the high-density chromosphere due to momentum conservation (e.g., Veronig et al 2010;Brosius & Inglis 2017;Tian & Chen 2018;Sellers et al 2022). That is, the upflows driven by chromospheric evaporation and the downflows caused by chromospheric condensation can be simultaneously observed in an explosive evaporation event.…”
Section: Introductionmentioning
confidence: 99%